Pelatihan pencegahan intoksikasi kadmium pada pekerja bengkel las di Kota Mataram - Bayu Tirta Dirja; Devi Rahmadhona; Decky Aditya Zulkarnaen (INDRA: Jurnal Pengabdian kepada Masyarakat, 2021)
Cadmium (Cd) is a nephrotoxic heavy metal which endangers human health, especially welding workers. Cadmium can enter the body through inhalation of formed air pollutants. Cadmium would then bind with metallotionins, binds Cd+Mt, which would be deposited in the kidneys and induces the formation of lipid-free radical peroxidation that damages the kidneys, characterized by an increase of creatinine and β2 microglobulins. This service aims to educate welding workers about the impact of cadmium intoxication on the body and the prevention against cadmium exposure. The methods used are demonstration and playback of a video about prevention against cadmium exposure. This activity was carried out on May 6th, 2021 at the CV. Rigansa Mataram welding workshop. The activity was attended by ten participants. The results are an increase of knowledge from a mean pretest score of 50 to a mean posttest score of 90